Public policy for pensions, health and sickness insurance. Potential lessons from Sweden for Latin America - Palmer, Edward (CEPAL SantiagoCL, 2006)
Discusses the rationale of social insurance and social insurance institutions as they have emerged and developed in economically mature nations. Examines key issues in system and institution design with reference to experiences from Sweden.